Polysaccharide‐rich hydrogel formulation combined with photobiomodulation repairs UV‐induced photodamage in mice skin. Issue 5 (26th June 2020) - Neves, Lia Mara Grosso; Parizotto, Nivaldo Antonio; Tim, Carla Roberta; Floriano, Elaine Medeiros; Lopez, Renata F Vianna; Venâncio, Tiago; Fernandes, João Batista; Cominetti, Marcia Regina
Abstract: Prolonged skin exposure to ultraviolet radiation (UVR) induces premature aging in both the epidermis and the dermis. Chronic exposure to UVR induces the activation of mitogen‐activated protein kinase (MAPK) signaling pathway, activating c‐Jun, c‐Fos expression, and transcription factor of AP‐1 activating protein. AP‐1 activation results in the positive induction of matrix metalloproteinase (MMP) synthesis, which degrade skin collagen fibers. Polysaccharides from the fruit of Lycium barbarum (LBP fraction) have a range of activities and have been demonstrate to repair the photodamage. In different approaches, laser application aims to recover the aged skin without destroying the epidermis, promoting a modulation, called photobiomodulation (PBM), which leads to protein synthesis and cell proliferation, favoring tissue repair. Here we developed a topical hydrogel formulation from a polysaccharide‐rich fraction of Lycium barbarum fruits (LBP). This formulation was associated with PBM (red laser) to evaluate whether the isolated and combined treatments would reduce the UVR‐mediated photodamage in mice skin. Hairless mice were photoaged for 6 weeks and then treated singly or in combination with LBP and PBM. Histological, immunohistochemistry, and immunofluorescence analyses were used to investigate the levels of c‐Fos, c‐Jun, MMP‐1, −2, and −9, collagen I, III, and FGF2. The combined regimen inhibited UVR‐induced skin thickening, decreased the expression of c‐Fos and c‐Jun, as well as MMP‐1, −2, and −9 and concomitantly increased the levels of collagen I, III, and FGF2. The PBM in combination with LBP treatment is a promising strategy for the repair of photodamaged skin, presenting potential clinical application in skin rejuvenation.